METTL3 regulates autophagy of hypoxia-induced cardiomyocytes by targeting ATG7 - Linnan Li; Hao Cheng; Yufei Zhou; Di Zhao; Xiaoxue Zhang; Yajun Wang; Jianying Ma; Junbo Ge (Cell Death Discovery)
Abstract N6-methyladenosine (m6A) mRNA modification is the most common mRNA internal modification in eukaryotes, which participates in a variety of biological processes. However, the role of m6A methylation in regulating autophagy induced by ischemia and hypoxia remains to be widely investigated. Here, we investigated the impact of METTL3, a key m6A methyltransferase, on the autophagy regulation in ischemic and hypoxic cardiomyocytes, as well as in mice following acute myocardial infarction (AMI). METTL3 negatively regulated autophagy in cardiomyocytes under ischemia and hypoxia conditions. Silencing METTL3 enhanced autophagy and mitigated cardiomyocyte injury, whereas overexpression of METTL3 exerted the opposite effect. Mechanistically, METTL3 methylated ATG7 mRNA, a crucial autophagy-related gene, leads to the recruitment of the m6A-binding protein YTHDF2. Subsequently, YTHDF2 facilitated the degradation of ATG7 mRNA, consequently inhibiting autophagy and exacerbating cellular damage. Our study shed light on the pivotal role of METTL3-mediated m6A modification in the regulation of autophagy during AMI, providing novel insights into the functional significance of m6A methylation and its regulatory mechanisms.